FAKTOR YANG MEMPENGARUHI PELAPORAN WHISTLEBLOWINGINTERNAL DENGAN TINGKAT PENDIDIKAN SEBAGAI VARIABEL MODERASI PERSEPSI KARYAWAN DI PT. KRAKATAU STEEL (PERSERO) TBK - Ferri Dwi Raharjo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This studyaims to examine the influence of ethical climate, organizational commitment, personal cost, seriousness of wrongdoing with moderated education level on whistleblowing intentions. Sampling technique using purposivesampling method to employees of PT. Krakatau Steel (Persero) Tbk. The results of the analysis showed that ethical climate have significant effect on internal whistleblowing intentions where as organizational commitment, personal cost and seriousness of wrongdoing do not have significant effect on internal whistleblowing intentions.Keywords: Internal whistleblowing, ethical climate, organizational commitment, personal cost, seriousness of wrongdoing, education level.